O LÚDICO NA EDUCAÇÃO: A RUPTURA DA LUDICIDADE NOS PRIMEIROS ANOS DO ENSINO FUNDAMENTAL - ZAMBELLI, ORLANDO CESAR (2014)
This Master's thesis is focused on analyzing the possible rupture of playfulness in the early years of elementary school. The aim is to reflect on the play activities as a pedagogical tool and their collaboration for learning in this school phase considering the child's transition from early childhood education to the elementary school and its distinct peculiarities. The qualitative research comprises a literature work based on renowned authors on the subject, official documents and interviews with teachers working in these series, and expert in the field. The analysis of collected data allowed more precise considerations on the use of playfulness as a pedagogical tool in the early years of elementary school, as well as provide elements for understanding of its importance in this universe